Advocacy in the anglo-american legal system - Závada, Tomáš (2006)
As the bulk of this thesis has made clear, there are countless careers in law. Individuals with legal training have a wide variety of career options available to them. When combined with extralegal skills and experience, law school graduates can work in many different roles. At the same time there are many opportunities within the legal profession for individuals who do not have formal law school training. College students considering careers in law should not think that law school is their only option. There are advantages and disadvantages to going to law school. It may be possible to work in a law office or perform law-related work in many jobs where bar membership is not a prerequisite. This thesis has described different facets of careers in law: the type of service rendered, the type of organization providing the service, the location of the organization and service, the substantive field of law, the critical skills required to perform the service, and the type of position or pa.